2012
DOI: 10.4155/bio.12.290
|View full text |Cite
|
Sign up to set email alerts
|

Development of A Fast Method for Direct Analysis of Intact Synthetic Insulins in Human Plasma: The Large Peptide Challenge

Abstract: A simple SPE LC-MS analysis was developed for direct, simultaneous quantification of insulin glargine, detemir, aspart and glulisine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 23 publications
1
34
0
Order By: Relevance
“…The presence of a carrier protein, such as BSA, in the dilution solvent can reduce adsorption of peptides at surfaces by occupying the nonspecific binding sites of materials used during standard preparation [23,39]. However, when adding 40 g mL −1 of BSA to the optimal dilution solvent (water/FA 95/5 V/V) aspecific adsorption of NT, NMB and NMN is not influenced in a regular Eppendorf tube (data not shown).…”
Section: Influence Of Bovine Serum Albumin (Bsa)mentioning
confidence: 93%
See 2 more Smart Citations
“…The presence of a carrier protein, such as BSA, in the dilution solvent can reduce adsorption of peptides at surfaces by occupying the nonspecific binding sites of materials used during standard preparation [23,39]. However, when adding 40 g mL −1 of BSA to the optimal dilution solvent (water/FA 95/5 V/V) aspecific adsorption of NT, NMB and NMN is not influenced in a regular Eppendorf tube (data not shown).…”
Section: Influence Of Bovine Serum Albumin (Bsa)mentioning
confidence: 93%
“…Due to aspecific adsorption of peptides to material used during standard preparation (pipette tips, Eppendorf tubes and UHPLC vials), the limit of quantification of the method is drastically affected [19,20]. In addition, it has been shown that the adsorption phenomenon is the main cause of poor repeatability and non-linearity in quantitative analyses of low-concentrated peptides [21][22][23][24]. Although stable isotope-labeled internal standards are able to correct for these two issues, they cannot correct for the loss of peptides due to adsorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The final gradient condition for insulin analysis was a linear gradient ramp from 25-55% B in 5 min. At analytical (2.1mm ID) scale, the literature [19,20,22,23] suggests that either a 300 Å pore size and/or positively charged surface particle columns might provide a further enhancement in sensitivity and peak shape. Therefore three 150 μm × 50 mm iKeys were compared under constant gradient conditions to rapidly confirm stationary phase choice.…”
Section: Resultsmentioning
confidence: 99%
“…For peptide analytes, it has been shown that both flow rate and solvent composition influence the relative abundances of the precursor ions formed [43,44]. Therefore, 1 μM standard solutions of NT, NMB and NMN, prepared in the solvent in which the peptides more or less elute, water/ACN/FA (50/50/0.1 V/V/V), are infused into the nano source at 300 nl/min, the flow rate used for separation.…”
Section: Compound-specific Ms/ms Parametersmentioning
confidence: 99%